Degas in New Orleans, October 1872-March 1873 [videorecording] - Goldman, Goldman L.; Phoenix Films ([S.l.] Master Vision, 1976)
Focuses on French artist Edgar Degas and his visit to New Orleans in 1872.
Title on cassette: Degas, Erte and Chagall.
Keywords: Degas, Hilaire Germain Edgar; Painters -- France -- Biography; Painters -- Louisiana -- New Orleans; Art studies; Humanities